Plants Biodiversity of Jobolarangan Forest Mount Lawu: 2. Spermatophyta - SUTARNO SUTARNO; AHMAD DWI SETYAWAN; SUHAR IRIANTO; APRIANA KUSUMANINGRUM (Biodiversitas Journal of Biological Diversity, 2001)
The objectives of the research were to make: (1) a list of Spermatophyte plants at Jobolarangan forest in mount Lawu, and (2) the ecological and the economical benefits of the plants. All Spermatophyte plants on the forest were studied. The research procedures were including species collection in the field, make up herbaria, morphological observations in the laboratory, and interview to residents and government administrations. The results showed that in the forest were found 142 species Spermatophyte plants, in which 126 species of 54 family were identified, consisting of 78 species of herbs, 26 species of bushes, and 21 species of trees. Ecological benefits of the plants were hydrological regulation, keep out landslide and erosions etc., however economical benefits of the plants were log, firewood, charcoal, honey bee, medicinal plants, etc.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: biodiversity, Spermatophyte plants, Jobolarangan forest, mount Lawu.